The influence of distributive, procedural, and interactional justice on motivation: Job satisfaction as a mediating variable - Fitriani, Fitriani; Hasanudin, Hasanudin; Mayasari, Endah; Shalahuddin, Ahmad (Junal Ilmu Manajemen, 2025)
Organizational justice is one of the important factors in increasing job satisfaction and encouraging employee motivation. The purpose of this study was to see how the influence of distributive justice, procedural justice, and interactional justice on work motivation and job satisfaction as mediating variables. The sampling technique used a census involving all employees of the Regional Revenue Agency of West Kalimantan Province, namely 43 respondents. Data analysis used Structural Equation Modeling (SEM) with SmartPLS 4. The results showed that distributive and interactional justice had a positive and significant effect on job satisfaction and motivation. However, procedural justice only had a positive effect on job satisfaction and had no effect on motivation. On the other hand, job satisfaction was shown to mediate the influence of distributive justice, procedural justice and interactional justice on motivation. The practical implications of these findings can help organizations improve justice management and job satisfaction to support overall employee motivation.